The Impact of Comorbidities on the Outcomes of Egyptian COVID-19 Patients: A Follow-Up Study. (19th June 2021) - Albadawy, Reda M.; Jadoon, Bismeen A.; Mogahed, Mysara M.; Ibrahim, Mohamed E.; Essawy, Tarek S.; Amin, Ahmed M. A.; Abd-Elraouf, Marwa S.; Elawady, Mona A.
Abstract : Objectives . This study evaluated the clinical manifestation of COVID-19 and adverse outcomes in patients with comorbidities (outcome: death). Methods . A comparative follow-up investigation involving 148 confirmed cases of COVID-19 was performed for a month (between April and May 2020) at Qaha Hospital to describe the clinical characteristics and outcomes resulting from comorbidities. Participants were divided into two clusters based on the presence of comorbidities. Group I comprised cases with comorbidities, and Group II included subjects without comorbidity. Survival distributions were outlined for the group with comorbidities after the follow-up period. Results . Fever (74.3%), headache (78.4%), cough (78.4%), sore throat (78.4%), fatigue (78.4%), and shortness of breath (86.5%) were the most prevalent symptoms observed in COVID-19 patients with comorbidities. Such patients also suffered from acute respiratory distress syndrome (37.8%) and pneumonia three times more than patients without comorbidities. The survival distributions were statistically significant (chi-square = 26.06, p ≤ 0.001 ). Conclusion . Multiple comorbidities in COVID-19 patients are linked to severe clinical symptoms, disease complications, and critical disease progression. The presence of one or more comorbidities worsened the survival rate of patients.